(untitled) (Medico Legal Update, 2020)
The problem of population in Indonesia is complex. Population policy in the era of decentralization is still not integrated and sustainable. Grand Design of Population Development is a guideline for population-oriented policies, strategies and development programs, which contains important current population issues, desired population conditions, population development programs, population development roadmaps covering population quantity control, quality development population, family development, spatial planning and population regulation and population administration development. Approach Grand Design of Population Development can influencing policy and responsive policy towards population dynamics. With the Grand Design of Population Development, a region can prepare itself to welcome the demographic bonus that can be done through improving human quality. Human development as an effort to develop capability the ability of human self, which contains four elements, namely productivity, equity, sustainability and empowerment. The roadmap set out in Grand Design of Population Development will be implemented on an ongoing basis to improve human quality, reflected in the increasing Human Development Index.